The Better to Eat You With: Bite Force in the Naked Mole-Rat (Heterocephalus glaber) Is Stronger Than Predicted Based on Body Size - Hite, Natalee J.; Germain, Cody; Cain, Blake W.; Sheldon, Mason; Perala, Sai Saketh Nandan; Sarko, Diana K. (Frontiers in Integrative Neuroscience, 2019)
Naked mole-rats (Heterocephalus glaber) are subterranean rodents that utilize their incisors for feeding, chisel-tooth digging of complex tunnel systems, social interactions, and defense in their eusocial colony structure. Previous studies have shown that naked mole-rats have morphological and anatomical adaptations that predict strong bite forces, namely skulls that are relatively tall and wide, in addition to impressive masticatory musculature. However, no studies to date have directly measured bite force in this species or analyzed the relationship between bite force and social caste. In the current study, we assessed adult naked mole-rat maximum bite force in relation to body mass, in addition to considering each animal’s position within the eusocial hierarchy (i.e., dominant vs. subordinate). Each animal was permitted to freely interact with a piezo-resistive bite force sensor. Our results showed that bite force was correlated with body mass in subordinate but not in dominant naked mole-rats, and that subordinate animals exhibited a shorter latency in producing their first bite. Maximum bite force was significantly influenced by caste. In comparing bite force with available data from previous studies across 82 additional mammalian species, subordinate naked mole-rats exhibited a bite force that was 65% higher than predicted for their body size, comparable to Tasmanian devils and exceeding bite force values for all of the carnivorans included for comparison. These results supported the hypothesis that the naked mole-rat’s bite force would exceed predictions based on body size due to the behavioral importance and specialization of the naked mole-rat incisors. This study provides insight into the differences in bite force across species, and the significant role that social and ecological factors might play in the evolutionary relationship between bite force performance and underlying anatomical structures.